Adopting social commerce elements: a comparison of Social Networking Site (SNS) and E-Commerce Site / Habiel Zakariah - Zakariah, Habiel (2014)
Social Commerce is a phenomenon in the ongoing E-commerce evolution through the adoption of Web 2.0 capabilities to improve customer participation and achieve successful business. Despite the trends of Social Commerce which highly anticipate todays the understanding on the appropriate platform is not clear. There is little research on Social Commerce adoption as mostly the researchers are more likely to explain on the theoretical background. This study will look on the Social Commerce elements adoption in the two different platforms of Ordinal E-Commerce website (standard E-Commerce website) and the Facebook Page (Social Networking Site) to see which one is better in terms of marketing and business management. The Social Commerce elements that will be analyze and compare are Forum & Community, Recommendation & Referral, Rating & Review and Social Advertising as the key elements of Social Commerce to market effectively. Later on comparison can be used for better overview of Social Commerce elements and its function as well the best practices to market in nowadays business culture.